EMPLOYMENT AND TOURISM IN LIMÓN Y PUNTARENAS: CASE STUDIES IN SELECTED - Cordero Ulate, Allen (2013)
The main aspect of the article introduce subjects about employment generated by tourism in historical and traditional tourism destinations, in other words, “domestic tourism”. The reference has been taken from three case studies - neighborhoods-; el barrio El Carmen, el barrio Juanito Mora –central canton of Puntarenas-; and  barrio Pacuare -central canton of Limón. Although the employment generated by tourism in these domestic destinations, is close to the 12% of the economically Local Active Population, the evidence indicate that this percentage is lower compared with neighborhoods that are close to international destinations; should be noted that the absolute weight of the employment is very important because one of the characteristics of these places is their large concentration of population. The study of the  employment in these districts also involves other labor segments, such as: fishing, formal sector, public sector, among others.